Polydopamine encapsulated new indocyanine green theranostic nanoparticles for enhanced photothermal therapy in cervical cancer HeLa cells - Fan, Huimin; Yan, Ting; Chen, Shuang; Du, Zhong; Alimu, Gulinigaer; Zhu, Lijun; Ma, Rong; Tang, Xiaohui; Heng, Youqiang; Alifu, Nuernisha; Zhang, Xueliang (Frontiers in Bioengineering and Biotechnology, 2022)
Photothermal therapy (PTT) has attracted extensive attention in cancer treatment due to its non-invasiveness, high efficiency, and repeatability in recent years. Photothermal agents (PTAs) are the key factor for PTT. Recently, although an increasing number of PTAs have been developed, there is still a great demand for optimized photothermal nanoparticles (NPs) with low toxicity, bio-safety and stability. Herein, new indocyanine green (IR820) with near-infrared (NIR:700-1700 nm) fluorescence emission was selected as a photothermal agent (PTA). To enhance the PTT property, IR820 was encapsulated with another kind of PTA, polydopamine (PDA) under alkaline conditions. Furthermore, to improve the biocompatibility of the NPs, methoxy polyethylene glycol amine (mPEG-NH2) was modified via a Michael addition to form a novel kind of IR820@PDA@PEG NPs. After detailed characterization and analysis, the obtained IR820@PDA@PEG NPs showed a spherical shape with an average diameter of ~159.6 nm. Meanwhile, the formed IR820@PDA@PEG NPs exhibited better photostability and lower cytotoxicity than free IR820 molecules. The photothermal performance of IR820@PDA@PEG NPs was further analyzed in vitro, and the temperature of IR820@PDA@PEG NPs (100 μg/mL) reached 54.8 ℃ under 793 nm laser irradiation. Afterwards, the cellular uptake of IR820@PDA@PEG NPs was evaluated via confocal laser scanning fluorescence microscopic imaging. Then, PTT experiments on HeLa cells was demonstrated that IR820@PDA@PEG NPs can hyperthermal ablate cancer cells (~48.3 %) under 793 nm laser irradiation. Therefore, IR820@PDA@PEG NPs would be a promising PTA for the treatment of cervical cancer HeLa cells.